A Review on Complications Confronted with Skin Penetration and Assessment of Topical Formulations in Dermal Drug Development - Gadde, Kalikrishna Praveen; Alex, Angel Treasa; Joesph, Alex (Indian Journal of Pharmaceutical Education and Research, 2019)
A topical drug-delivery system is the most accepted drug delivery system. One of the pre-requisites for a topical formulation is its ability to penetrate the skin membrane to elicit the intended action. Many in vitro skin permeation studies are reported by scientists to evaluate the penetration of the drug into human skin. Several direct methods including tape stripping, in vitro percutaneous studies measures skin tissue concentration. While indirect methods like plasma collection, micro-dialysis etc. the information produced is translated and transformed to offer details of skin tissue concentration. The present review focuses on various techniques in use for the estimation of topical drugs to assess skin permeation, along with their merits and demerits and challenges encountered in them. Additionally, this review also focus on limitations in topical drug development.
Keywords: Skin permeation; Microdialyis; in vitro Percutaneous Studies; Tape stripping; Skin contamination